2012
DOI: 10.1155/2012/518263
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Insufficient Sleep and Self-Rated Health in a Nationally Representative Sample

Abstract: Reduced sleep has been found to be associated with increased risk of diabetes mellitus, hypertension, cardiovascular disease (CVD), and mortality. Self-rated health (SRH) has been shown to be a predictor of CVD and mortality. However, study of the association between insufficient sleep and SRH is limited. We examined participants >18 years of age (n = 377, 160) from a representative, cross-sectional survey (2008 BRFSS). Self-reported insufficient sleep in the previous 30 days was categorized into six groups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
36
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 17 publications
8
36
0
2
Order By: Relevance
“…Distinct from short sleep duration, insufficient sleep has recently been linked to poor self-rated health 61 . Women who reported insufficient sleep for 14 or more out of the past 30 days had the highest risk of poor health.…”
Section: 2650-52mentioning
confidence: 99%
“…Distinct from short sleep duration, insufficient sleep has recently been linked to poor self-rated health 61 . Women who reported insufficient sleep for 14 or more out of the past 30 days had the highest risk of poor health.…”
Section: 2650-52mentioning
confidence: 99%
“…1 Organisation for Economic Co-operation and Development (OECD) reported sleep time on an average day in min in 18 OECD countries. That fi gure for Koreans was about 470 min, which was the shortest among the surveyed nations.…”
mentioning
confidence: 99%
“…3,4 Normal sleep is vital for human functioning and well-being. Sleep problems in various general populations with and without chronic diseases have been associated with poorer self-rated health 5 and with increased mortality. 6,7 Without appropriate treatment, sleep problems can become persistent, as reported by Morin et al, 8 who found that 49% of patients with insomnia symptoms at baseline had insomnia symptoms at the 1-year follow-up as well.…”
mentioning
confidence: 99%